E-learning in Croatia: Possibility of Mobile Multimedia Systems for Distance Learning - Vuksanović, Irena (Array, 2007)
New mobile network technology allows broadcasting of broadband services interactive to multimedia communications users, firstly to always on generation which is driven by early old age technology and to whose first members were the leading communication technology users capable for development of new multimedia education. The fact is that education and following processes are knowledge market and competition, recognized on global level today. Information communication technology offers new possibilities for improving existing education system. Distance education method carries numerous possibilities in every day organization of education process from almost unlimited, time and space, communication possibilities to learning method. Having that in mind, it is important to find the best possible provision of new methods and adequately, according to the conditions and needs, incorporate in education system. This presentation is about Croatian achievement in information communication technology implementation (ICT) into education system and Republic of Croatia possibilities for usage of distributed mobile multimedia education systems for distance learning.